Anxiety as a risk factor of tension type headache - Wahyuliati, Tri; Afifudin, Lutfi (Science Midwifery, 2024)
Tension-type headache is a primary headache frequently encountered by young individuals. Anxiety is a contributing factor to tension-type headaches. A rigorous curriculum and schedule, transfers within the educational system, competitive academic performance, and similar factors induce anxiety among medical students. This study aims to assess the impact of anxiety on tension-type headaches. We conducted a cross-sectional study that included 73 medical students who were preparing for the Objective Structured Clinical Examination (OSCE). Data was collected about 2-5 days before the OSCE at the final tutorial. Anxiety is assessed using the Hamilton Anxiety Rating Scale (HARS). At the same time, tension-type headaches are identified via the ICHD III criteria. A total of 73 individuals exhibiting anxiety were examined. Specifically, mild anxiety was observed in 13 participants (17.8%), moderate anxiety in 7 subjects (9.6%), severe anxiety in 21 subjects (28.8%), and highly severe anxiety in 32 subjects (43.8%). Among the 73 participants, 26 (35.6%) suffered tension-type headaches, while 47 (64.4%) did not. The Spearman Rank test revealed a correlation coefficient of r = 0.263 and a p-value of 0.025 (<0.05), indicating a weak yet significant association. Anxiety exhibits a weak yet substantial link with the occurrence of tension-type headaches.